Thinking with certainty or with doubt: a Lacanian theorisation of discursive knowledge in teacher education. Issue 3 (4th May 2019) - Hanley, Chris; Brown, Tony
ABSTRACT: The paper presents a theorisation of pedagogic knowledge formation, as a continuous attempt to understand the positions in discourse we occupy. The paper documents some participatory practitioner research by teacher educators centred on a course development initiative for student teachers of English, at an English university. Students researched their experiences of becoming a teacher within a course that was largely school-based, whilst their tutors researched their own involvement in the process (the main focus of this paper). Drawing on Lacanian theory, tutors are depicted as learning subjects having more or less certainty or doubt about the knowledge they possess. In attempting to understand this interplay of certainty and doubt, tutors arrive at stronger conceptualisations of learning. Through this approach, the paper provides a theoretically informed conception of professional knowledge, as involving a process of renewing ideas about learning, in meeting or resisting external demands.